Dynamic correlation pattern amongst alternative energy market for diversification opportunities - Mobeen Ur Rehman (Journal of Economic Structures, 2020)
Last couple of decades witnessed recognition of energy markets as investment commodities which led interest of the international investment community. We investigate the potential of globally diverse alternative energy markets for optimal returns by analysing their correlation pattern. Our study employs daily data spanning from January 2006 to December 2017. To estimate pairwise return co-movement, we employ rolling window multiple wavelet correlation based on decomposed returns using maximal overlap discrete wavelet transformation to infer implications for both short- and long-run investors. We witness maximum diversification between developed (World, Devel-oped, EU, G7) and emerging (BRIC, Emerging) markets. Most of these combinations exhibit no traces of contagion during the financially and economically turbulent periods. Finally, we use non-linear causality test to highlight increased integration between our sampled alternative energy indices after financial and economic crises periods. Our results carry implications for short- and long-run investors as well as for policy makers.
Keywords: 330; Alternative energy markets; Rolling window wavelets; Wavelets transformation